Immunohistological expression of human ß‐defensin‐1 and human ß‐defensin‐2 in exacerbation of acute and secondary chronic osteomyelitis of the mandible. (16th June 2014) - Beck‐Broichsitter, Benedicta E.; Dau, Heino; Moest, Tobias; Jochens, Arne; Stockmann, Philipp; Wiltfang, Jörg; Becker, Stephan T.
<x xml:space="preserve">Abstract</x> Background The majority of patients diagnosed with osteomyelitis of the jaw have severe complaints. Unfortunately, the pathogenesis still remains unclear. Human ß‐defensins expressed in epithelial and bone tissues as a part of the innate immunity may be involved in disease development. In this study, we hypothesize that expression levels of human ß‐defensin‐1 and ‐2 in the acute and secondary chronic osteomyelitis may be altered in comparison with healthy bone and with bisphosphonate‐associated necrosis as well as irradiation from a previous study. Methods Bone samples were collected during surgical debridement in a total of eight patients suffering from acute or secondary chronic osteomyelitis of the jaw. Expression levels of hBD‐1 and ‐2 were quantified and related to non‐stained cells. Ratios were compared by one‐way ANOVA and multiple tests by Holm–Bonferroni. Results Multiple testing revealed no significant differences for expression levels of human ß‐defensin‐1 between all groups, whereas labeling index of human ß‐defensin‐2 was significantly different between specimens of bisphosphonate‐associated osteonecrosis of the jaws and all other groups. No significant difference occurred between samples of floride osteomyelitis and healthy bone for expression of hBD‐1 and ‐2. Conclusions Although the affected patients showed all clinical signs of acute inflammation, expression levels in acute and secondary chronic osteomyelitis in the jaws did not reveal statistically significant differences compared with healthy bone samples. The weak immunological host response in terms of a putative genetically predisposition should be further discussed as pathogenesis factor for osteomyelitis in the future.